The interplay between the measured dimension and temperature of hot large forgings. Issue 9 (December 2015) - Zhang, Fu-li; Zhang, Yu-cun; Zhang, Lei-qiang; Hou, Xin-yu
Abstract During the forming process of hot forgings, the dimension and temperature are key parameters for improving the forging technology. In the paper, based on the mathematical physics methods, a mutual relationship model between the measured dimension and the temperature is proposed. This relationship model is displayed by the temperature field model and the dimensional model. Firstly, according to the law of conversation of energy, using the Dirichlet function and the measured dimension, the power-transfer function of heat source is established. Taking the measured temperatures as the boundary conditions, the temperature field model influenced by the dimensional change is established using the method of the moving virtual heat source. Secondly, based on the variation characteristics between the mesoscopic structure and the stress, using the function of the deformation energy is analyzed. Using the differential calculus of the pluralistic function, the dimensional change model influenced by the measured temperature is established. Based on the temperature field model and the dimensional model, this mutual relationship of the two ones can be clearly and directly displayed. Finally, the verifiable experiments and simulations are obtained using the forging experiments and the Deform-3D. Using the contrastive analysis method, the feasibility of the two relationship models is verified and the change trends of the dimension and temperature are analyzed. Combining the parameters of the forging technology in the thermal forming process, the application and the practical significance of the model are further cleared. The mutual relationship model provides a theoretical basis for improving the forging technology.